Serum Isthmin-1 levels are positively correlated with macrovascular complications in type 2 diabetic patients - Yajing Wang; Yajing Wang; Yingjie Feng; Yingjie Feng; Xue Wang; Xue Wang; Xicui Zong; Jing Liu; Jing Liu; Shujin Liang; Shujin Liang; Yiqun Meng; et al. (Frontiers in Endocrinology, 2025)
ObjectiveIsthmin-1 (ISM-1), a novel adipokine, has dual effects of increasing fat and glucose uptake while inhibiting hepatic fat synthesis. However, little literature has been found dealing with ISM-1 levels in type 2 diabetes patients with macroangiopathy. The aim of the study was to evaluate possible relationships between ISM-1 peptide levels and macrovascular (MACV) complications in type 2 diabetic subjects.MethodsThe study groups consisted of 20 normal controls (NC), 20 T2DM subjects, and 65 MACV subjects. Serum ISM-1 concentrations were determined using immunosorbent assay kits. Linear regression analysis was used to assess the correlation between serum ISM-1 levels and glucose and lipid indicators.ResultsThe results showed that the serum ISM-1 levels were higher in T2DM subjects than normal controls but lower than MACV subjects (1.20 (0.86, 1.83) vs. 2.07 (1.06, 4.09), P<0.0001). In addition, positive correlations were found between: ISM-1 and systolic blood pressure (SBP) (r = 0.2934; P= 0.0024), ISM-1 and diastolic blood pressure (DBP) (r = 0.2041; P= 0.0368), ISM-1 and triglyceride (TG) (r = 0.3388; P= 0.0004), ISM-1 and FBG (r = 0.2586; P= 0.0077), ISM-1 and HbA1c (r = 0.4002; P< 0.0001), ISM-1 and TyG index (r = 0.3342; P= 0.0005), ISM-1 and HOMA-IR (r = 0.2558; P = 0.0085) in both MACV, T2DM and normal control subjects. Negative correlations were found between ISM-1 and high-density lipoprotein cholesterol (HDL-C) (r = -0.4065; P< 0.0001) and ISM-1 and HOMA-IS (r = -0.2106; P = 0.0319) in both subjects.ConclusionsOur results indicated that MACV individuals have higher serum ISM-1 levels, and ISM-1 was positively correlative to glucolipid metabolism and blood pressure, suggesting ISM-1 may participate in the occurrence and development of MACV mainly by affecting glucose and lipid metabolism